Биология летяги на юге Тюменской области - Nizovtsev, D. S.; Gashev, S. N.; Низовцев, Д. С.; Гашев, С. Н. (Издательство Тюменского государственного университета, 2013)
We have carried out a pioneer investigation on the assessment of the population of the Siberian flying squirrel in Tyumen region in 2007-2010 by recording its waste. The habitat area of the flying squirrel in Tyumen region stretches from the northern taiga (inclusive) to its southern borders in the forest-steppe zone. The maximum density of the flying squirrel population is registered in the southern taiga subzone. 44 sites have been studied in total. 31,8% of all the observed sites are inhabited by the Siberian flying squirrel. All habitats are connected with the transfer zone from the plain land to the river lowland and marsh. As a rule this transfer zone is significantly clean-boled. The flying squirrel adheres to such tree breeds as a birch, pine cedar, firtree, aspen and linden. The species has been seen in the forest park of Tyumen city. The morpho-physiological parameters testify to internal stability of the squirrel population found in favorable ecological conditions. Пионерные работы по оценке обилия летяги методом учета ее экскрементов проведены в 2007-2010 гг. в Тюменской области. Ареал обыкновенной летяги в Тюменской области простирается от северной тайги (включительно) до ее южных границ в зоне лесостепи. Максимальная плотность вида приурочена к южнотаежной подзоне. Обследовано 44 участка, обитаемыми из них оказались 31,8%. Все местообитания связаны с переходом от плакора к пойме или болоту, как правило, значительно осветленным. Летяга придерживается таких пород деревьев как береза, сосна кедровая, ель, осина и липа. Отмечено обитание вида в лесопарке г. Тюмени. Морфофизиологические параметры свидетельствуют о внутреннем стабильном состоянии популяции, находящейся в благоприятных экологических условиях.